Innovation of the Polish economy in comparison with the EU member states - Magdalena Węglarz (Economic and Environmental Studies (E&ES), 2018)
In the paper, the change in the innovation level of the Polish economy over the years 2007-2016 will be presented and a comparison of the innovation level between the Polish economy and those of the EU member states over the years 2010-2016 will be made. The aim of the paper is to find the answer to the question what the reason of the relatively low innovation level of the Polish economy is in comparison with other countries. In 2016, the Polish economy took the fourth place from the last among all the EU member states, reaching the innovation level of less than 55% relative to that of the EU in 2010. In the first part, a measurement of innovation of the Polish economy will be presented. The measurement will use indicators that were described in three different reports of the Central Statistical Office. In the next part, the innovation level of all the EU member states will be described and the innovation level of the Polish economy will be compared with the innovation level of the EU member states' economies, such as: Sweden (SE), the Czech republic (CZ), Slovenia (SI) Lithuania (LT) and the European Union. The analysis will be made on the basis of data from European Innovation Scoreboard 2017 (EIS). The methodology that was used in EIS is based on OECD Frascati Manual. In the last part of the article, the evaluation of the innovation level of the Polish economy will be completed.
Keywords: O52; O57; O30; 330; innovation of economy; European Innovation Scoreboard